2009
DOI: 10.1016/j.bmc.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Enaminones 8: CoMFA and CoMSIA studies on some anticonvulsant enaminones

Abstract: Abstract3D QSAR studies comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) were carried out on 26 structurally diverse subcutaneous pentylenetetrazol (scPTZ) active enaminone analogues, previously synthesized in our laboratory. CoMFA and CoMSIA were employed to generate models to define the specific structural and electrostatic features essential for enhanced binding to the putative GABA receptor. The 3D QSAR models demonstrated a reliable ability to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…It was found that the Galβ(1 → 4)GlcNAc and the Fucα(1 → 3)GlcNAc linkages exhibited quite specific conformational minima, which agreed with the experimental values of Φ/ψ = −77.0/131.6° for Galβ(1 → 4)GlcNAc, and Φ/ψ = −53.4/−90.9° for Fucα(1 → 3)GlcNAc. The overall rigidity of these linkages has been found in previous computational and experimental investigations (Yuriev et al, 2005; Jackson et al, 2009; Agostino et al, 2010). The GlcNAcβ(1 → 3)Gal linkage exhibited broader minima, also in agreement with previous findings (Jackson et al, 2009).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…It was found that the Galβ(1 → 4)GlcNAc and the Fucα(1 → 3)GlcNAc linkages exhibited quite specific conformational minima, which agreed with the experimental values of Φ/ψ = −77.0/131.6° for Galβ(1 → 4)GlcNAc, and Φ/ψ = −53.4/−90.9° for Fucα(1 → 3)GlcNAc. The overall rigidity of these linkages has been found in previous computational and experimental investigations (Yuriev et al, 2005; Jackson et al, 2009; Agostino et al, 2010). The GlcNAcβ(1 → 3)Gal linkage exhibited broader minima, also in agreement with previous findings (Jackson et al, 2009).…”
Section: Resultssupporting
confidence: 68%
“…The overall rigidity of these linkages has been found in previous computational and experimental investigations (Yuriev et al, 2005; Jackson et al, 2009; Agostino et al, 2010). The GlcNAcβ(1 → 3)Gal linkage exhibited broader minima, also in agreement with previous findings (Jackson et al, 2009). The Ramachandran-like plots highlight that Glide, GOLD, and DOCK can effectively identify appropriate conformations of the Lewis X trisaccharide in the majority of instances; the experimentally determined conformations occur within the clusters obtained via the conformational search implementation of molecular docking.…”
Section: Resultssupporting
confidence: 68%
“…Meanwhile, several enaminones with chemical moieties different from KRS-5Me-4-OCF 3 were described to interact with GABA A receptors (Reitz et al, 1999;Yohannes et al, 2003;Hogenkamp et al, 2007). Other enaminone derivatives that probably target GABA receptors were provided by using the comparative molecular field analysis and comparative molecular similarity techniques, which can generate models to define the specific structural and electrostatic features essential for enhanced binding of enaminones to the putative GABA receptor (Jackson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The model of highest q 2 value and lowest standard error of prediction suggested the optimum number of components. Leave one out (LOO) cross-validation was used to estimate the predictive ability of the models (Jackson et al, 2009). …”
Section: Comfa and Comsiamentioning
confidence: 99%